Longitudinal Serial Mediation Study after the 2023 Earthquake in Türkiye: Associations Between Difficulties in Emotion Regulation, Psychological Distress, Resilience and Mental Well-Being - Okur, Sinan; Satici, Seydi Ahmet; Erdinc, Beste; Akyil, Yusuf (SPRINGER, 2025)
Although the concepts of mental well-being, difficulties in emotion regulation, resilience, and psychological distress have been investigated in cross-sectional studies, their absence from a longitudinal study demonstrates a gap in the literature. Following the earthquake disaster in T & uuml;rkiye, addressing these concepts together in a longitudinal study may offer important implications for the field of mental health. The longitudinal mediation of resilience and psychological distress in the relationship between difficulties in emotion regulation and mental well-being was investigated in a Turkish adult sample. The study sample consisted of 219 participants aged between 18 and 45 (51.1% male, Mage = 31.60, SD = 7.19). To avoid the limitations of cross-sectional studies, data for the current study were examined at three-month intervals and at two time points in a cross-lagged panel model with a half-longitudinal design to investigate the mediating role of resilience and psychological distress between difficulties in emotion regulation and mental well-being. The analysis found that resilience and psychological distress played a longitudinal mediating role in the relationship between emotion regulation challenges and mental well-being. In conclusion, people's ability to regulate their emotions, be resilient, and avoid psychological distress may improve their mental health. These findings underscore the importance of integrative interventions that simultaneously target difficulties in emotion regulation, resilience, and psychological distress to better support mental well-being in post-disaster contexts.
Keywords: Difficulties in emotion regulation; Psychological distress; Resilience; Mental well-being; Longitudinal serial mediation study; Psychiatry